Physician Attributes That Matter Most: Results from a Qualitative Inquiry of Oncologists, Patients Receiving Oncological Care, and Medical Students - Kimberly McMillan; Deborah Akurang; Paul Wheatley-Price (Current Oncology)
Background: Physician attributes significantly impact patient outcomes, satisfaction, and trust. Various attribute frameworks have been developed to help structure and guide undergraduate medical education and subsequent clinician practice; however, prioritization of these attributes vary by stakeholder (patients, physicians, medical students). Based on findings from two previous studies completed by the research team, we sought to understand the context in which individuals in these stakeholder groups prioritize particular physician attributes. We adopted a qualitative approach, conducting semi-structured interviews with patients (N = 11), doctors (N = 11), and medical students (N = 12), for a total sample of 34. Results: Thematic analysis of data resulted in the following five themes: caring, communicator, expert, professional, curiosity and open-mindedness. Central to our findings was the need for a positive, trusting provider–patient relationship, which was framed as the conduit to quality patient care (both receiving and providing). The attributes believed to support this central finding differed, noting that “caring”, “curiosity and open-mindedness” are not typical in physician attribute frameworks. Findings suggest there is a central guiding philosophy shaping what medical students, physicians and patients alike, need in the context of the provider–patient relationship, which transcends particular attributes. The guiding philosophy of relational inquiry is used to further situate study findings. Conclusions: Integrating a central guiding philosophy can add additional depth and nuance to attribute frameworks, ensuring considerations for qualities that transcend particular attribute characteristics, such as “caring” and “curiosity and open-mindedness” are also explicitly used to help structure and guide undergraduate medical education and subsequent clinician practice.